Nuisance and privacy - Nolan, D (Sweet and Maxwell, 2021)
Discusses Fearn v Tate Gallery Board of Trustees (CA) on whether interference with privacy was an actionable private nuisance, in the context of the overlooking of luxury flats from an art gallery's viewing platform. Details practical factors supporting the ruling, including the difficulty of distinguishing between acceptable and unacceptable overlooking, the grounds for dismissing ECHR art.8 claims, and the alternative remedies.